Stéréotypes animaux dans Le Roman de Renart - Giermak-Zielińska, Teresa (Neophilologica, 2006)
The author of the article analyzed linguistic stereotypes concerning human and animal features of the characters appearing in the medieval novel The Romance of Reynard the Fox (Roman de Renart), many scholars call these characters the “animallike people”. King Lion’s courtiers: Reynard the Fox, Ysengrin the Wolf and others are often called barons as they display customs and manners of knights. Despite this fact their deeds have nothing to do with chivalry and morality that one can read about in courtly literature. Quite the opposite, these characters are presented in a much more modern manner - as cunning, going back on their words, pusillanimous and cruel. The animal costumes created a comic or even burlesque effect which resulted from the clash of stereotypical animal features with the description of adventures happening in the world extremely similar to the real one. In this article one can find many examples illustrating the linguistic forms of these stereotypical images.